Pengaruh Beban Kerja Dan Kompensasi Terhadap Turnover Intention Karyawan Dengan Stress Kerja Sebagai Variabel Intervening : Studi Kasus Pada Karyawan Swasta Di Wilayah Kabupaten Tangerang - Siti Ayunah; Agung Solihin (CV ODIS, 2023)
This study aims to analyze the effect of workload on work stress. Analyzing the effect of workload on employee turnover intention. Analyzing the Effect of Compensation on Work Stress. Analyzing the Effect of Compensation on Employee Turnover Intention. Analyzing the Influence of Work Stress on Employee Turnover Intention. Analyzing the mediating role of Work Stress on the effect of Workload on Employee Turnover Intention. Analyzing the mediating role of Job Stress on the effect of Compensation on Employee Turnover Intention. The analytical method used is SEM-PLS analysis. The data collection technique uses a questionnaire distributed questionnaires to private employees in the Tangerang Regency area of 120 employees. The sampling technique used a random sampling method. The results of the study show that workload has a positive and significant effect on work stress and employee turnover intention. Compensation has a positive and insignificant effect on work stress and employee turnover intention. Work Stress can mediate the effect of Workload on Employee Turnover Intention. Work Stress cannot mediate the effect of Compensation on Employee Turnover Intention